CLIMATE CHANGE AND SECURITY: THE CASE FOR BLACK SEA - MIHAILOV, Maria-Emanuela; GRIGORESCU, Lucian; PERA, Romel (Strategic Impact, 2024)
Climate change poses significant challenges to global security by exacerbating existing threats and creating new ones. Competition over scarce resources such as food, water, and land will likely increase as extreme weather events and temperature rise will become more frequent. Climate-related migration is expected to increase political tensions, and in some regions, could contribute to instability and conflict. The changing climate will also impact infrastructure, the economy, and public health, which will have far-reaching security implications. The current issue of climate change highlights the spectre of a new source of instability and conflict that can affect national/international peace and security. Although comparative research and projects on the security implications of climate change are expanding, there are still major knowledge gaps. The paper presents the specialized literature on short-term climate change and its possible influence on the Black Sea regional security. It is increasing the potential insecurities that can arise from extreme environmental phenomena. Based on the assessment, the authors outline priorities for future research in the area of interest and cover the necessary adjustments to facilities, materials, and equipment due to progressive weather changes. It also highlights that natural disasters may increase in number or virulence, necessitating the contribution of armed forces to national security.